Prenatal opioid exposure and risk of asthma in childhood: a population-based study from Denmark, Norway, and Sweden - Odsbu, Ingvild; Handal, Marte; Hjellvik, Vidar; Hernandez-Diaz, Sonia; Kieler, Helle; Nørgaard, Mette; Skurtveit, Svetlana; Esen, Buket Öztürk; Mahic, Milada (Frontiers in Pharmacology, 2023)
Background: Opioids may modulate the immune function through opioid receptors on immune cells. Long-term consequences of prenatal opioid exposure on the immune system, such as childhood asthma, are unknown. Objectives: To investigate whether prenatal opioid exposure is associated with the risk of childhood asthma. Methods: Cohort study using linked nationwide registers in Denmark (1996-2015), Norway (2005-2015), and Sweden (2006-2013). Children born by mothers who were chronic opioid analgesics users before pregnancy (n = 14,764) or who were receiving opioid maintenance therapy (OMT) before or during pregnancy (n = 1,595) were identified based on information from each of the medical birth registers and prescription registers. Long-term opioid analgesics exposed children were compared to short-term exposed or unexposed, whereas OMT exposed children were compared to OMT unexposed. Asthma among children ≥1 years of age was defined as two or more filled prescriptions of antiasthmatic medication within 365 days, or a diagnosis of asthma. Hazard ratios (HRs) were calculated using Cox proportional hazards regression with attained age as the time scale. Inverse probability of treatment weights based on propensity scores were applied to adjust for measured confounders. Individual level data from Norway and Sweden were pooled, whereas individual level data from Denmark were analyzed separately. For the opioid analgesics comparisons, adjusted HRs (aHR) from the combined Norwegian/Swedish data and the Danish data were pooled in a fixed-effects meta-analysis. Results: For the opioid analgesics cohort, no increased risk of asthma was observed in long-term exposed children neither compared with unexposed (aHR = 0.99 [95% CI 0.87-1.12], nor compared with short-term exposed (aHR = 0.97 [0.86-1.10]). No increased risk of asthma was observed in OMT exposed compared with OMT unexposed children (Norway/Sweden: aHR = 1.07 [0.60-1.92], Denmark: aHR = 1.25 [0.87-1.81]). Results from sensitivity analyses, where potential misclassification of the outcome and misclassification of OMT exposure were assessed, as well as starting follow-up at 6 years of age, showed that the estimates of association were generally robust. Conclusion: We found no association between prenatal exposure to opioids and risk of childhood asthma. Results were consistent across two different opioid exposure groups with different confounder distributions.